2021
DOI: 10.7554/elife.67926
|View full text |Cite
|
Sign up to set email alerts
|

Role of BRCA2 DNA-binding and C-terminal domain in its mobility and conformation in DNA repair

Abstract: BRCA2 is an essential protein in genome maintenance, homologous recombination and replication fork protection. Its function includes multiple interaction partners and requires timely localization to relevant sites in the nucleus. We investigated the importance of the highly conserved DNA binding domain (DBD) and C-terminal domain (CTD) of BRCA2. We generated BRCA2 variants missing one or both domains in mouse ES cells and defined their contribution in HR function and dynamic localization in the nucleus, by sin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 63 publications
4
19
0
Order By: Relevance
“…As expected, cells that harbored the empty vector displayed hypersensitivity to MMC and Rucaparib (Fig. 5a), whereas expression of WT BRCA2 led to a marked enhancement of resistance to both DNA damaging agents 10,33,50,51 . However, cells expressing BRCA2 variants that harbor either the CTRB-F/A or 4 A mutation were clearly sensitized to MMC and Rucaparib, and, importantly, cells that expressed the double BRCA2 mutant exhibited higher sensitivity to these agents than either of the single mutants (Fig.…”
Section: Role Of Ctrb Attributes In Dna Damage Repair Hr and Rad51 Fo...supporting
confidence: 79%
“…As expected, cells that harbored the empty vector displayed hypersensitivity to MMC and Rucaparib (Fig. 5a), whereas expression of WT BRCA2 led to a marked enhancement of resistance to both DNA damaging agents 10,33,50,51 . However, cells expressing BRCA2 variants that harbor either the CTRB-F/A or 4 A mutation were clearly sensitized to MMC and Rucaparib, and, importantly, cells that expressed the double BRCA2 mutant exhibited higher sensitivity to these agents than either of the single mutants (Fig.…”
Section: Role Of Ctrb Attributes In Dna Damage Repair Hr and Rad51 Fo...supporting
confidence: 79%
“…How DNA damage signals for increased interaction between DPP9 and BRCA2 remains to be shown. However, we note that the N‐terminus of BRCA2 is intrinsically disordered (Le et al , 2020 ; Sidhu et al , 2020 ; Paul et al , 2021 ) and is involved in the formation of BRCA2 dimers and multimers through self‐interactions (Shahid et al , 2014 ; Reuter et al , 2015 ; Sánchez et al , 2017 ; Le et al , 2020 ; Sidhu et al , 2020 ). Thus, it is tempting to speculate that BRCA2 is shielded from DPP9 in the multimeric form, and becomes available as a DPP9 substrate by a transition of BRCA2 multimers to monomers, a process that is favored by ssDNA, RAD51, increased temperature, and the BRCA2 chaperone DSS1 (Le et al , 2020 ; Sidhu et al , 2020 ).…”
Section: Discussionmentioning
confidence: 96%
“…The DBD is the most conserved part of the BRCA2 protein, from fungi to humans, 41 but its function is less clear than other more 'recent' BRCA2 regions. 24 Biochemistry and microscopic studies highlighted the importance of this domain for conformation rearrangements of BRCA2 and its interaction with DNA repair partners. 24,42,43 In vitro, deletion of DBD but not the Cterminal domain of BRCA2 similarly leads to increased sensitization to platinum salts and PARPi.…”
Section: Discussionmentioning
confidence: 99%
“…24 Biochemistry and microscopic studies highlighted the importance of this domain for conformation rearrangements of BRCA2 and its interaction with DNA repair partners. 24,42,43 In vitro, deletion of DBD but not the Cterminal domain of BRCA2 similarly leads to increased sensitization to platinum salts and PARPi. 24 Studies investigating the distribution of secondary mutations of BRCA2 that restore the open reading frame of the protein, a common mechanism of secondary resistance to platinum and PARPi in patients, [44][45][46][47][48] showed that reversion mutations in BRCA2 exhibit a position dependence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation